Analisis Kendala Penawaran dan Kebijakan Revitalisasi Produksi Padi - Maulana, Mohamad; Simatupang, Pantjar; Syafa’at, Nizwar (Jurnal Agro Ekonomi, 2006)
EnglishDecreasing and decelerating production capacity of paddy have caused decreasing of estate capacity in food supply. This paper aims at describing production overview, problems and policy options to increase paddy production. Analysis methods uses in this study are cross tabulation and econometric model for projection. The results show that decreasing of paddy production growth rate was affected by: (a) decreasing of paddy’s planted/harvested? area, especially in Java and (b) stagnation or decreasing of land productivity. Based on historical tendency, and when the revitalization program of national rice industry is not effective, projection result shows that rice production will have negative growth rate during the period of 2006-2010 and import will increase during the same period. Government policy to increase production capacity in rice industry should be oriented to shift from price policy to focus on increasing capacity of production, i.e., (a) rehabilitation and extensification in irrigation infrastructure, (b) expansion of new land for paddy, and (c) acceleration of technology innovation, including revitalization of research and development and dissemination of agriculture innovation system along with deregulation and creation of conducive environment for private investors.IndonesianPenurunan dan deselarasi kapasitas produksi padi telah menyebabkan kemampuan negara dalam menyediakan pangan menurun. Kajian ini bertujuan untuk menyajikan dinamika produksi, masalah dan kendala, serta opsi kebijakan peningkatan produksi padi. Metode analisis yang digunakan dalam kajian ini adalah tabulasi silang dan model ekonometrika untuk menduga fungsi penawaran. Hasil analisis menunjukkan kecenderungan penurunan laju pertumbuhan produksi padi adalah akibat dari kombinasi: (a) penurunan luas baku lahan sawah, khususnya di Jawa, dan (b) kemandekan, bahkan penurunan produktivitas lahan. Berdasarkan kecenderungan historis dan bila program revitalisasi industri perberasan nasional tidak efektif, diperkirakan produksi beras akan mengalami pertumbuhan negatif pada periode tahun 2006-2010 dan Indonesia akan terpaksa mengimpor beras dalam jumlah yang semakin besar. Kebijakan pemerintah dalam meningkatan kapasitas produksi industri perberasan nasional harus diorientasikan dari fokus kebijakan harga ke peningkatan kapasitas produksi, melalui: (a) rehabilitasi dan ekstensifikasi infrastruktur irigasi; (b) pembukaan lahan sawah baru; dan (c) memacu inovasi teknologi, termasuk revitalisasi sistem penelitian dan pengembangan pertanian serta sistem diseminasi inovasi pertanian dengan deregulasi dan penciptaan iklim kondusif bagi investor swasta.